Desain User Interface ‘Disaster Spatial Learning Global Partnership’ - Lauw, Aaron Christoperus Prayogo; Susilowati, Meme; Handoyo, Budi (Yayasan Kita Menulis, 2026)
This article presents the design of the User Interface (UI) for the DSL Global Partnership (DSLGP) system, a Web-GIS–based educational platform developed to support disaster literacy and digital learning. The study focuses on translating the Software Requirements Specification into structured UI components, including the Home page, role-based dashboards, and key transactional workflows such as guest registration, assessment distribution, resource validation, and data import operations. The UI is designed using a user-centered approach, emphasizing clarity, accessibility, and role separation to ensure intuitive navigation for research teams, teachers, students, administrators, and public users. This work provides a concise and systematic overview of the UI structure that can guide subsequent implementation and evaluation stages within the DSLGP development cycle.